A study of four cases of physician participation in terminally ill patients' suicides: factors that may contribute to a physician's decision - Stone, Kirby L., author; Morgan, George A., advisor; Foster, Ann, committee member; Banning, James H., committee member; Phillips, Dennis D., committee member (Colorado State University. Libraries, 2000)
The purpose of this study was to identify and understand the factors that contribute to a physician's decision to participate in a terminally ill patient's suicide. To accomplish this, four published stories by two physicians who agreed to participate in terminally ill patients' suicides were analyzed using a cross-case study methodology. Due to the continued advancements in medical technologies, our life expectancy has increased, causing us to suffer from more illnesses. Many of these illnesses are degenerative and debilitating over time, making people die a prolonged death. Because of the prolonged dying process and the suffering that comes along with it, people are asking their physicians to participate in helping them control their own deaths. Previous studies show that some physicians do consent to assist with their patient's suicide, and some show that a higher percentage of physicians support the legalization of physician-assisted suicide than those that do not. Four common factors contributing to a physician's decision to participate in a terminally ill patient's suicide were identified. The four factors are: 1) Physician/patient relationship, 2) Physician/patient communication, 3) Physician/patient progression together through patient's disease, and 4) Physician understanding/acceptance of patient's personal definition of suffering. Each of the four stories in this study clearly demonstrated the four identified factors. The physician and patient developed a personal and professional relationship over a period of time. Together they worked through the different stages of the patient's illness, which enabled the physicians to understand and accept the patient's definition of suffering. The trust between the physician and the patient developed because of their ability to communicate openly and honestly, leading to the accomplishment of the other three factors.
Keywords: health; health education; health sciences